Globalization, culture, class and mobile phone usage. Issue 1 (1st October 2013) - Ciochetto, Lynne
This article is intended to address a deficit in current information about new technology user patterns in the 'developing world'. Western media primarily focuses on high-income western industrialized societies and ignores most other counties. Reporting on the Third World, especially Africa, is preoccupied with disasters, famines and conflict (disaster porn). General information and good news stories about the Third World are seen as of 'low interest' to western audiences. Research into patterns of media use in the field of cultural studies also tends to be preoccupied with developed countries, and recently there has been particular focus on the iPhone. This article explores the diversity in the international profile of mobile phone users across cultures and classes using seven case studies: Kenya, India, Brazil, China, Russia, New Zealand and the United States. This study is intended to demonstrate – through a review of literature and information from international databases – how user patterns vary widely cross-culturally, even in developed countries. The explanation for these variations is traced back to economics, cultural values and the wider socio-political context. Patterns in mobile phone use are closely related to social class and incomes, which in turn reflect the way people work and use their leisure time. Major differences occur between owning a mobile phone – or 'feature phone' – versus a smartphone. In the past, mobile phone usage was limited to texting and calling plus a few other features, while smartphones offer a much greater diversity of functions because of their access to the Internet. Differences between the two types of phone are diminishing as more mobile phones have access to the mobile web. The relatively high cost of smartphones means income levels play a key role in patterns of ownership. Because standards of living are higher in the developed world the class background of smartphone users is broader than in the developing world where ownership is concentrated in the affluent and middle classes. Cost remains the major consideration in most countries. In 2013 the popularity of the iPhone is being challenged by new competition from Samsung, as competition between 'features' intensifies.